(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2021)
The bioinvader bivalve Corbicula fluminea (Müller, 1774) is known in the Río de la Plata River since about 35 years ago. This time lapse fills a gap in taphonomical studies, that comprises usually strictly contemporaneous or at best centuries-old phenomena. We sampled shells of this species in one locality in two occasions with the same methodology. Fragmentation, presence of periostracum, corrasion, bioerosion and bioencrustation were studied externally in four sectors of the valve: umbonal, anterior, central, and posterior. We tested the differences in the frequencies of the attributes between the two samples by means of Χ2, resulting only significantly different corrasion in the umbonal sector and fragmentation in the central and posterior areas.The umbonal area was the most affected sector, and it was attributed to a higher exposition to corrasive agents (i.e., moving clasts) compared to other areas of the valve. Neither bioerosion nor bioencrustation was recorded, being this attributed to the less prevalence of these taphonomic features in the low salinity conditions of the study area.